HEAVY METALS AND TRACE ELEMENTS LEVELS AND ITS RISK ASSESSMENT IN TWO EDIBLE FISHES FROM WADI HANIFAH, RIYADH, SAUDI ARABIA - Fahad A. Al-Misned; M. Golam. Mortuza (Journal of Animal and Plant Sciences, 2015)
African catfish (Clarias gariepinus) and Sabaki tilapia (Orechromis spilurus) were collected from Wadi Hanifah (Riyadh, Saudi Arabia) and samples of muscle, skin, and gills were analyzed for Be, Cr, Mn, Fe, Co, Ni, Pb, Cu, Zn, As, Se, Sr, Mo, Cd, Sb, and Tl using inductively coupled plasma mass spectrometry (ICP-MS) to highlight the importance of species and tissue selection in monitoring research, contaminant studies, and human health risk assessment. All the heavy and trace elements were found to be below the international permissible standards. The Arsenic (As) levels in the muscles of both the fishes were generally higher, but none of the elements exceeded the permissible limit. The estimated daily intake (EDI) was below the reference dose (RfD) established by the US-EPA and the hazard quotient values indicated that there was no carcinogenic risk for humans.
Keywords: Heavy metal; trace element; risk assessment; edible fish; and Wadi Hanifah